2013
DOI: 10.1021/cm401232r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rb and Ta Doping on the Ionic Conductivity and Stability of the Garnet Li7+2xy(La3–xRbx)(Zr2–yTay)O12 (0 ≤ x ≤ 0.375, 0 ≤ y ≤ 1) Superionic Conductor: A First Principles Investigation

Abstract: In this work, we investigated the effect of Rb and Ta doping on the ionic conductivity and stability of the garnet Li 7+2x−y (La 3−x Rb x )(Zr 2−y Ta y )O 12 (0 ≤ x ≤ 0.375, 0 ≤ y ≤ 1) superionic conductor using first principles calculations. Our results indicate that doping does not greatly alter the topology of the migration pathway, but instead acts primarily to change the lithium concentration. The structure with the lowest activation energy and highest room temperature conductivity is Li 6.75 La 3 Zr 1.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
138
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 36 publications
14
138
0
Order By: Relevance
“…These results are consistent with other simulation studies. 25,26,29 In the case of Ga atoms (for x = 0.30), their MSD starts to increase at 1200 K (Figure 5c). This onset temperature for Ga ion diffusion does not vary with respect to Ga content (see Figure S4 in the Supporting Information).…”
Section: +mentioning
confidence: 98%
See 2 more Smart Citations
“…These results are consistent with other simulation studies. 25,26,29 In the case of Ga atoms (for x = 0.30), their MSD starts to increase at 1200 K (Figure 5c). This onset temperature for Ga ion diffusion does not vary with respect to Ga content (see Figure S4 in the Supporting Information).…”
Section: +mentioning
confidence: 98%
“…The trajectory of the x = 0 case is in strong agreement with a recent analysis of neutron powder diffraction data 62 as well as several simulation studies. [25][26][27]29 To make a clear comparison with the x = 0.30 case, we chose an appropriate slab section to expose the full 2D plane view of Li pathway connectivity, such as plane (3 6 4), which is shown in blue in Figure 10a and 10c. As can be seen, pathway features such as junctions formed by Td sites (LiO 4 ) and density lobes formed by Oh sites (LiO 6 ) can be observed in detail (Figure 10b, d).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, pentavalent (e.g., Ta 5+ , Nb 5+ ) ion doping on the Zr sites will stabilize the cubic phase and enhance the ionic conductivity. 109,113,114 Trivalent dopants (e.g., Ga 3+ ) on either the Li sublattice or La sites can also stabilize the cubic phase, 114,115 but very limited improvement in ionic conductivity is observed for La site doping. 114 Using AIMD simulations, Miara et al 113 further demonstrated that the ionic conductivity can be maximized by tuning the dopant (and hence Li) concentration in doped LLZO.…”
Section: Llzo Garnetmentioning
confidence: 99%
“…Nevertheless, there have been recent successes in computational dopant optimizations for solid electrolyte materials. 113,130 Despite significant progress, existing computational methods for probing alkali diffusion-ab initio and classical MDs, transition state theory and kinetic Monte Carlo (KMC)-all suffer from various limitations. Ab initio methods, such as NEB and AIMD, tend to be computationally expensive, whereas methods that depend on empirical or fitted potentials, such as classical MD and KMC, while much cheaper computationally, are difficult to transfer between chemistries and structures.…”
Section: Computational Studies Of Alkali Conduction Z Deng Et Almentioning
confidence: 99%